Skip to content
Related Articles

Related Articles

Improve Article

Class 11 RD Sharma Solutions – Chapter 12 Mathematical Induction – Exercise 12.2 | Set 3

  • Last Updated : 20 May, 2021

Question 33. Prove that n11/11 + n5/5 + n3/3 – 62/165n is true for all n ∈ N.

Solution:

Let, P(n) = n11/11 + n5/5 + n3/3 – 62/165n

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Step 1:



Now, let us check P(n) for n = 1.

So, P(1) = 1/11 + 1/5 + 1/3 – 62/165 = 1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m,

Let, P(m) = m11/11 + m5/5 + m3/3 – 62/165m

So, m11/11 + m5/5 + m3/3 – 62/165m = λ, where λ ∈ N is a positive integer.

Step 3:

Now, we have to prove for P(m + 1) is true.

P(m + 1) = (m + 1)11/11 + (m + 1)5/5 + (m + 1)3/3 – 62/165(m + 1)

= 1/11(m11 + 11m10 + 55m9 + 165m8 + 330m7 + 462m6 + 462m5 + 330m4

165m3 + 55m2 + 11m + 1) + 1/5(m5 + 5m4 + 10m3 + 10m2 + 5m + 1) + 

1/3(m3 + 3m2 + 3m + 1) + 62/165(m + 1)

= λ + m6 + 3m5 + 5m4 + 5m3 + 3m2 + m + m4 + 2m3 + 2m2 + m + m2 + m + m + 1

As λ is positive, so it is a positive integer.

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.



Question 34. Prove that (1/2)tan(x/2) + (1/4)tan(x/4) +…..+ (1/2n)tan(x/2n) = (1/2n)cot(x/2n) – cotx for all n ∈ N and 0< x < π/2.

 Solution:

Let, P(n) = (1/2)tan(x/2) + (1/4)tan(x/4) +…..+ (1/2n)tan(x/2n) = (1/2n)cot(x/2n) – cotx, for all n ∈ N and 0< x < π/2.

Step 1:

Now, let us check P(n) for n = 1.

LHS = 1/2 tan(x/2)

RHS = (1/2)cot(x/2) – cot(x) = 1/(2tan(x/2)) – 1 tan(x)

= 1/(2tan(x/2)) – 1/(2tan(x/2))/(1 – tan2(x/2))

= 1/(2tan(x/2)) – (1 – tan2(x/2))/(2tan(x/2))

=(1/2)tan(x/2)

So, P(1) is true.



Step 2:

Let us consider P (n) be the true for n = m,

P(m) = (1/2)tan(x/2) + (1/4)tan(x/4) +…..+ (1/2m)tan(x/2m) = (1/2m)cot(x/2m) – cotx

Step 3:

Now, we have to prove for P(m + 1) is true.

P(m + 1) = (1/2)tan(x/2) + (1/4)tan(x/4) +…..+  (1/2m)tan(x/2m) + (1/2(m + 1))tan(x/2(m + 1)) = (1/2(m + 1))cot(x/2(m + 1)) – cotx

So, = (1/2m)cot(x/2m) – cotx + (1/2(m+1))cot(x/2(m+1))

= (1/2m)cot (x/2m) + (1/2(m+1))tan(x/2(m+1)) – cotx

= 1/(2mtan(2x/2(m+1)) + (1/2(m+1))tan(x/2(m+1)) – cotx

= [(1 – tan2(x/2(m+1)))/2(m+1).tan(x/2(m+1))] + (1/2(m+1))tan(x/2(m+1)) – cotx

= (1/2(m+1))cot(x/2(m+1)) – cotx

Now,

(1/2)tan(x/2) + (1/4)tan(x/4)+…..+ (1/2m)tan(x/2m) + (1/2(m+1))tan(x/2(m+1)) = (1/2(m+1))cot(x/2(m+1)) – cotx

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 35. Prove that (1 – 1/22)(1 – 1/32)(1 – 1/42)……(1 – 1/n2) = (n + 1)/2n is true for all n ∈ N.

Solution:

Let, P(n) =  (1 – 1/22)(1 – 1/32)(1 – 1/42)……(1 – 1/n2) = (n + 1)/2n

Step 1:

Now, let us check P(n) for n = 2.



P(2) = 1 – 1/22 = (2 + 1)/2.2

or, 3/4 = 3/4

So, P(2) is true.

Step 2:

Let us consider P (n) be the true for n = k, So, P(k) is

P(k) =  (1 – 1/22)(1 – 1/32)(1 – 1/42)……(1 – 1/k2) = (k + 1)/2k

Step 3:

Now, we have to prove for P(k + 1) is true. i.e. 

P(k + 1) = (1 – 1/22)(1 – 1/32)(1 – 1/42)……(1 – 1/(k + 1)2) = (k + 2)/2k

Now, (1 – 1/22)(1 – 1/32)(1 – 1/42)……(1 – 1/k2)(1 – 1/(k + 1)2)

Now, from step 2, we get

So, (1 – 1/(k + 1)2)((k + 1)/2k)

or, ((k + 1)/2k)((k2 + 1 + 2k – 1)/(k + 1)2

or, k(k + 2)/2k(k + 1)

or, (k + 2)/2(k + 1)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 36. Prove that (2n)!/22n(n!)2 ≤ 1/√(3n + 1) is true for all n ∈ N.

Solution:

Let, P(n) = (2n)!/22n(n!)2 ≤ 1/√(3n + 1) 

Step 1:

Now, let us check P(n) for n = 1.

P(1) = 1/2 ≤ 1/√3 + 1 = 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m.

P(m) = (2m)!/22m(m!)2 ≤ 1/√(3m + 1) 

Step 3:

Now, we have to prove for P(m + 1) is true. i.e. 

P(m + 1) = (2m + 2)!/22m+2(m!)2 ≤ 1/√(3m + 4)  



Now,

P(m + 1) = ((2m + 1)(2m + 1)(2m)!)/(2m2.22(m + 1)2(m!)2)

or, (2m + 2)!/2{2m + 2}((m + 1)!)2 = ((2m)!/22m) × (2m + 1)(m + 2)/22(m + 1)2

or, (2m + 2)!/2{2m + 2}((m + 1)!)2 ≤ (2m + 1)/2(m + 1)√(3m + 1)

or, (2m + 2)!/2{2m + 2}((m + 1)!)2 ≤ √((2m + 1)2/4(m + 1)2(3m + 1))

(2m + 2)!/2{2m + 2}((m + 1)!)2 ≤ √((2m + 1)2/4(m + 1)2(3m + 1))

or, (2m + 2)!/2{2m + 2}((m + 1)!)2 ≤ √(12m3 + 28m2 + 19m + 4)/(12m3 + 28m2 + 20m + 4)(3m + 4)

now, (12m3 + 28m2 + 19m + 4)/(12m3 + 28m2 + 20m + 4) < 1

so, (2m + 2)!/2{2m + 2}((m + 1)!)2 ≤ 1/√(3m + 4)

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 37. Prove that 1 + 1/4 + 1/9 + 1/16 + …..+ 1/n2 < 2 – 1/n for all n > 2, n ∈ N.

Solution:

Let P(n) = 1 + 1/4 + 1/9 + 1/16 + …..+ 1/n2 < 2 – 1/n for all n > 2, n ∈ N

Step 1:

Now, let us check P(n) for n = 2.

P(2) = 1/22 < 2 – 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m.

P(m) = 1 + 1/4 + 1/9 + 1/16 +…..+ 1/m2 < 2 – 1/m

Step 3:

Now, we have to prove for P(m + 1) is true. i.e.,

From step 2 we have, 1 + 1/4 + 1/9 + 1/16 +…..+ 1/m2 < 2 – 1/m 

Now, adding 1/(m + 1)2 to both the sides, we get

= 1 + 1/4 + 1/9 + 1/16 +…..+ 1/m2 + 1/(m + 1)2 < 2 – 1/m + 1/(m + 1)2

or, (m + 1)2 > m + 1

or, 1/(m + 1)2 < 1/(m + 1)

or, 1/m – 1/(m + 1)2 < 1/(m + 1)

So, P(m + 1) < 2 – 1/(m + 1)

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 38. Prove that x2n-1 + y2n-1 is divisible by x + y.

Solution:

Let, P(n) be   x2n-1 + y2n-1

Step 1:

Now, let us check P(n) for n = 1.

P(1) = x + y  

So, P(1) is divisible by x + y.

So, P(1) is true.



Step 2:

Let us consider P (n) be the true for n = m.

P(m) = x2m-1 + y2m-1= λ(x + y)         ……….. (i)

Step 3:

Now, we have to prove for P(m + 1) is true. 

i.e. ,  P(m + 1) = x2m+1 + y2m+1

= x2m+1 + y2m+1 – x2m-1. y2  +  x2m-1 . y2

= x2m-1(x2 – y2) + y2(x2m-1+y2m-1)

= (x + y)(x2m-1 (x – y) + λy2)

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 39. Prove that sinx + sin3x + …+ sin(2n – 1)x = sin2nx/sinx is true for all n ∈ N.

Solution:

Let, P(n) =  sinx + sin3x + …+ sin(2n – 1)x = sin2nx/sinx

Step 1:

Now, let us check P(n) for n = 1.

P(1) = sin x = sin2 x / sin x = sin x

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m.

P(m) =  sinx + sin3x + …+ sin(2m – 1)x = sin2mx/sinx

Step 3:

Now, we have to prove for P(m + 1) is true.

i.e., 

P(m + 1) = sinx + sin3x +…+ sin(2m – 1)x + sin(2m + 1)x = (sin2mx/sinx) + sin(2m+1)x

now,

P(m + 1) = {(sin2mx + sinx[sin(mx) + cos(m + 1)x + sin(m + 1)x + cos(mx)])}/sinx

= {(sin2mx + 2sinx.cosx.cos(mx) – sin2x.sin2mx + cos2mx.sin2x)}/sinx

= {(sin2mx(1 – sin2x) + 2sinx.cosx.cos(mx) + cos2mx.sin2x)}/sinx

= {(sin2mx.cos2x + 2sinx.cosx.cos(mx) + cos2mx.sin2x)}/sinx

= {(sin(mx).cosx + cos(mx).sinx)2}/sinx

= {(sin(m + 1)x)2}/sinx  

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 40. Prove that cosα + cos(α +β) +cos(α +2β)+....+cos(α +(n-1)β)=\frac{(cos[α +(\frac{n-1}{2})β] sin(\frac{nβ}{2}))}{sin(\frac{β}{2})}  is true for all n ∈ N.

Solution:

Let, P(n) = cosα + cos(α +β) +cos(α +2β)+....+cos(α +(n-1)β)=\frac{(cos[α +(\frac{n-1}{2})β] sin(\frac{nβ}{2}))}{sin(\frac{β}{2})}

Step 1:

Now, let us check P(n) for n = 1.

L.H.S = cos [α + (1 – 1)β] = cos α



R.H.S =\frac{(cos[α +(\frac{1-1}{2})β] sin(\frac{β}{2}))}{sin(\frac{β}{2})} = cosα

So, P(1) is true as LHS and RHS are equal.

Step 2:

Let us consider P (n) be the true for n = k.

P(k) = cosα + cos(α +β) +cos(α +2β)+....+cos(α +(k-1)β)=\frac{(cos[α +(\frac{k-1}{2})β] sin(\frac{kβ}{2}))}{sin(\frac{β}{2})}

Step 3:

Now, we have to prove for P(k + 1) is true.

So, adding cos(α + kβ) both sides of P(k), we get

P(k+1)= cosα + cos(α +β) +cos(α +2β)+....+cos(α +(k-1)β) +cos(α +kβ)=\frac{(cos[α +(\frac{k-1}{2})β] sin(\frac{kβ}{2}))}{sin(\frac{β}{2})}+cos(α +kβ)

=\frac{(cos[α +(\frac{k-1}{2})β] sin(\frac{kβ}{2})+cos(α +kβ)sin(\frac{β}{2})}{sin(\frac{β}{2})}



=\frac{(-sin(α-\frac{β}{2}) + sin(α+kβ+\frac{β}{2}))}{2sin(\frac{β}{2})}

=\frac{2cos(\frac{(2α +kβ)}{2})sin(\frac{(kβ+β)}{2})}{2sin(\frac{β}{2})}

=\frac{cos(α +\frac{kβ}{2})sin(\frac{(k+1)β}{2})}{sin(\frac{β}{2})}

Now,

RHS= \frac{(cos[α +(\frac{kβ}{2})] sin(\frac{(k+1)β}{2}))}{sin(\frac{β}{2})}

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 41. Prove that 1/(n+1) + 1/(n+2) +…..+ 1/2n > 13/24 for all natural numbers, n > 1.

Solution:-

Let,P(n) = 1/(n+1) + 1/(n+2) +…..+ 1/2n > 13/24

Step 1:

Now, let us check P(n) for n = 2.

P(2) = 1/(2 + 1) + 1/(2 + 2) = 1/3 + 1/4 = 7/12 > 13/24

So, P(2) is true.

Step 2:

Let us consider P (n) be the true for n = k, So, P(k) is

P(k) = 1/(k + 1) + 1/(k + 2) +…..+ 1/2k > 13/24

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

So, P(k + 1) = 1/(k + 2) + 1/(k + 3) +…..+ 1/2k + 1/2(k + 1)

Here, as LHS = RHS

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 42. Given a1 = 1/2(a0 + A/a0), a2 = 1/2(a1 + A/a1) and an+1 = 1/2(an + A/an), a, A > 0

To prove: \frac{(a_n - √A)}{(a_n + √A)}  = (\frac{ a_1 - √A}{a_1 + √A})^{2^{(n-1)}}

Solution:

Let, P(n) = \frac{(a_n - √A)}{(a_n + √A)}  = (\frac{ a_1 - √A}{a_1 + √A})^{2^{(n-1)}}

Step 1:

Now, let us check P(n) for n=1.

LHS = (a1 – √A) / (a1 + √A) 

RHS = (\frac{ a_1 - √A}{a_1 + √A})^{2^{(1-1)}}



= (a1 – √A) / (a1 + √A)

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k, So, P(k) is

So, P(k) = \frac{(a_k - √A)}{(a_k + √A)}  = (\frac{ a_1 - √A}{a_1 + √A})^{2^{(k-1)}}

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

So, P(k + 1) = LHS = (ak+1 – √A) / (ak+1 + √A)

=  (1/2(ak + A/ak) – √A) /  (1/2(ak + A/ak) + √A) 

= (1/2(ak2+ A – 2ak√A)/ak ) / (1/2(ak2+ A + 2ak√A)/ak )

=  (ak+1 – √A)2 / (ak+1 + √A)2

[ [\frac{a_1 - √A}{a_1 + √A}]^{2^{k-1}}]^2 

[\frac{a_1 - √A}{a_1 + √A}]^{2^k}

here, as LHS = RHS

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 43. Let P(n) be the statement: 2n ≥ 3n. If P(r) is true then show that P(r + 1)is true, Do you conclude that P(n) is true for all n ∈ N?.

Solution:

Let P(n) = 2n ≥ 3n

Step 1:

Now, let us check P(n) for n = 1.

L.H.S = 2

R.H.S = 3

As L.H.S < R.H.S

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = r, So, P(r) is 2r ≥ 3r

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

So, P(k + 1) = 2r+1 = 2.2r

For, x > 3, 2x > x + 3

So, 2.2r > 2r+3 for r > 1

or,2r+1 > 2r+3 for r > 1

or, 2r+1 > 3r +3 for r > 1

or, 2r+1 > 3(r + 1) for r >1

So, P (n) is true for n = r + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 44. Show by the principle of Mathematical Induction that the sum Sn of the n terms of the series 12 + 2 × 22 + 32 + 2 × 42 + 52 + 2 × 62 + 72 +… is given by 

S_n=  \begin{cases}    \frac{n(n+1)^2}{2}, if \ n \ is \ even, \\    \frac{n^2(n+1)}{2}, if \ n \ is \ odd \end{cases}

Solution:

Let, P(n) = Sn = 12 + 2 × 22 + 32 + 2 × 42 + 52 + 2 × 62 + 72 +… = \begin{cases}   \frac{n(n+1)^2}{2}, if \ n \ is \ even, \\   \frac{n^2(n+1)}{2}, if \ n \ is \ odd \end{cases}



Step 1:

Now, let us check P(n) for n = 1.

LHS = 1 = RHS

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k, So, P(k) is

P(k) = 12 + 2.22 + 32 + 2.42 + 52\begin{cases}   \frac{k(k+1)^2}{2}, if \ k \ is \ even, \\   \frac{k^2(k+1)}{2}, if \ k \ is \ odd \end{cases}

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

Case1: When k is odd, then (k + 1) is even

P(k + 1) = LHS = 12 + 2.22 + 32 + 2.42 + 52…. k2 + 2.(k + 1)2

= k2(k + 1)/2 + 2.(k + 1)2

= {(k2(k + 1) + 4(k + 1)2)}/2

= (k + 1)(k + 2)2/2

now, RHS = (k + 1)(k + 1 + 1)2/2

= (k + 1)(k + 2)2/2

So, it is true for n = k + 1, when k is odd.

Case 2: When k is even, then (k + 1) is odd

P(k + 1) = LHS = 12 + 2.22 + 32 + 2.42 + 52….+ 2. k2 + (k + 1)2

= k(k + 1)2/2 + (k + 1)2

= (k(k + 1)2 + 2.(k + 1)2)/2

= (k + 1)2(k + 2)/2

RHS = (k + 1)2(k + 1 + 1)/2

= (k + 1)2(k + 2)/2

now, LHS = RHS.

So, it is true for n=k+1, when k is even.

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 45.  Prove that the number of subsets of a set containing n distinct elements is 2n for all n ∈ N.

Solution:

Let, P(n): The number of subsets of a set containing n distinct elements = 2n, for all n ∈ N.

Step 1:

Now, let us check P(n) for n = 1.

LHS = As, the subsets of the set containing only 1 element are:

Φ and the set itself

i.e. the number of subsets of a set containing only element=2

R.H.S = 21 = 2

now, LHS = RHS

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

So, P(k) is The number of subsets of a set containing k distinct elements = 2k

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

P(k + 1) = Let A = {a1, a2, a3, a4,..…, ak, b} so that A has (k + 1) elements.

Now, the subset t of A can be divided into two collections such that 

First contains subsets of A which don’t have b in them and

The second contains subsets of A which do have b in them.

So, First collection: {}, {a1}, {a1, a2}, {a1, a2, a3},…,{a1, a2, a3, a4,…, ak} and

and the second collection: {b}, {a1, b}, {a1, a2, b}, {a1, a2, a3, b},…,{a1, a2, a3, a4,…,ak, b}

It can be clearly seen that:

The number of subsets of A in first collection

= The number of subsets of set with k elements i.e. {a1, a2, a3, a4,…, ak} = 2k

Also, it follows that the second collection must have

the same number of the subsets as that of the first = 2k

So the total number of subsets of A = 2k + 2k = 2k+1

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 46. A sequence a1, a2, a3,….. is defined by letting a1 = 3 and ak = 7ak-1 for all numbers natural numbers k ≥ 2. Show that an = 3.7n-1 for all n ∈ N.

Solution:



Let P(n) be an = 3.7n-1 for all n ∈ N

Step 1: 

Now, let us check P(n) for n = 1.

so, a1 = 3.71-1 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = ak = 3.7k-1

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

P(k + 1) = ak+1 = 7.ak

= 7.3.7k-1

= 3.7k-1+1

= 3.7(k+1)-1

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 47. A sequence x1, x2, x3,….. is defined by letting x1 = 2 and xk = xk-1 /k for all numbers natural numbers k, k ≥ 2. Show that xn = 2/n! for all n ∈ N.

Solution:

Let, P(n) be xn = 2/n!  for all n ∈ N.

Step 1:

Now, let us check P(n) for n = 1.

P(1) = x1 = 2/1! = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = xk = 2/k! 

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

so,  xk+1 = 2/(k + 1)! 

or, 2/(k + 1).k!

or, 2/(k + 1)!

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 48. A sequence x0, x1, x2, x3, ……. is defined by letting x0 = 5 and xk = 4 + xk -1 for all natural number k. Show that xn = 5 + 4n for all n ∈ N using mathematical induction.

Solution:- 

Let, P(n) = xn = 5 + 4n for all n ∈ N

Step 1:

Now, let us check P(n) for n = 0.

P(0) = 5 + 4(0) = 5

So, P(0) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = xk = 5 + 4k  

Step 3:

Now, we have to prove for P(k + 1) is true. When P(k) is true.

so, P(k + 1) = xk+1 = 4 + xk+1 -1

= 4 + xk

= 4 + 5 + 4k

= 5 + 4(k + 1) 

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

Question 49. Using principle of mathematical induction prove that

√n < 1/√1 + 1/√2+ 1/√3 +…..+1/√n for all natural numbers n ≥2.

Solution:

Let, P(n) = √n < 1/√1 + 1/√2+ 1/√3 +…..+1/√n for all n ≥ 2.

Step 1:

Now, let us check P(n) for n=2.

P(2) = √2 < 1 + 1/√2

or, 1.41 < 1 + 0.707 = 1.707

So, P(2) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = √k < 1/√1 + 1/√2+ 1/√3 +…..+1/√k

Step 3:

Now, we have to prove for P(k+1) is true. When P(k) is true.

Now, LHS = √(k + 1)

Now, RHS = 1/√1 + 1/√2+ 1/√3 +…..+1/√k + 1/√(k + 1)

or, k/√{(k + 1)} < √k

or, k + 1/√{(k + 1)} – 1/√(k + 1) < √k

or, √(k + 1) – 1/√(k + 1)< √k

or, √(k + 1) < √k + 1/√(k + 1)

so, LHS < RHS.

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ≥ 2

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ≥ 2.

Question 50. The distributive law from algebra states that for all real numbers, a1 and a2, we have c (a1 + a2) = ca1 + ca2. Use this law and mathematical induction to prove that, for all natural numbers, n ≥ 2, if c, a1, a2,…,an are any real numbers, then c (a1+a2+…+an) = ca1+ca2+…+can.

Solution:

Let, P(n) = c (a1+a2+…+an) = ca1+ca2+…+can, for all natural numbers, n ≥ 2. 

Step 1: 

Now, let us check P(n) for n=2.

LHS = c(a1 + a2)

RHS = c a1 + ca2

So, P(2) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) =  c(a1+a2+…+ak) = ca1+ca2+…+cak

Step 3:

Now, we have to prove for P(k+1) is true. When P(k) is true.

LHS = c(a1+a2+…+ak + ak+1)

= c[(a1+a2+…+ak) + ak+1]

= c(a1+a2+…+ak) + cak+1

= ca1+ca2+…+cak + cak+1

= RHS

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ≥ 2

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ≥ 2.




My Personal Notes arrow_drop_up
Recommended Articles
Page :